Drug Information Retrieval among Surgeons: Overlooked or Axiomatic? - Gabriel Rodrigues 1 & Sohil Ahmed Khan2 (Archives of Global Professionals, 2010)
With the passage of time and the innovations in the field of medicine the drug literature is expanding massively and getting complex due to its inter-disciplinary and inter professional nature. The accelerating pace of change in medicine stems from a progression of scientific information and the need to blend this information into the art and practice of medicine. Particularly speaking in context of surgery the access and retrieval of drug information is a very critical issue.It is seen that with the passage of time the drug information process for the surgeons has become more complex than the past. Hospitals and professional bodies require a culture that supports surgeons in their quest for knowledge, and provides the technological and educational environment in which they can promote evidence-based surgery [1]. In addition the identification of clinical problems and critical appraisal of the literature need to be taught either by incorporating its components in the curriculum or by organizing Continuous Medical Education (CME) Sessions which will help in making the drug information process more robust.